Contact Intensity, Unemployment and Finite Change - The Case of Entertainment Sector under Pandemic: A General Equilibrium Approach - Sugata Marjit; Gouranga Das (Global Labor Organization (GLO), 2022)
This paper explores the short run, medium run and long run impact of pandemic on the contact intensive entertainment industry in terms of a simple general equilibrium model that can accommodate for unemployment and underemployment. Finite change as a response to large shocks may lead to vanishing occupations in this industry, even when pandemic is over and leads to underemployment. Pandemic tends to eliminate fixed wage contracts in this sector for its survival, but over the longer run affects fundamental occupational choice in a society.
Keywords: F22; J31; O15; 330; Wage gap; Covid-19; Entertainment; Contact-intensive; Finite Change; General Equilibrium